Seismic localization of elephant rumbles as a monitoring approach. Issue 180 (14th July 2021) - Reinwald, Michael; Moseley, Ben; Szenicer, Alexandre; Nissen-Meyer, Tarje; Oduor, Sandy; Vollrath, Fritz; Markham, Andrew; Mortimer, Beth
Abstract : African elephants ( Loxodonta africana ) are sentient and intelligent animals that use a variety of vocalizations to greet, warn or communicate with each other. Their low-frequency rumbles propagate through the air as well as through the ground and the physical properties of both media cause differences in frequency filtering and propagation distances of the respective wave. However, it is not well understood how each mode contributes to the animals' abilities to detect these rumbles and extract behavioural or spatial information. In this study, we recorded seismic and co-generated acoustic rumbles in Kenya and compared their potential use to localize the vocalizing animal using the same multi-lateration algorithms. For our experimental set-up, seismic localization has higher accuracy than acoustic, and bimodal localization does not improve results. We conclude that seismic rumbles can be used to remotely monitor and even decipher elephant social interactions, presenting us with a tool for far-reaching, non-intrusive and surprisingly informative wildlife monitoring.